Determinants of Decisions to Implement Digital Payments for MSME Actors: A Study of Technological, Organizational, and Environmental Theory - Dewanto, Marcus; Rita, Maria Rio (MediaTrend, 2023)
Micro, Small, and Medium Enterprises (MSMEs) play an essential role in the Indonesian economy. However, many MSME actors, particularly those in Salatiga City, have yet to integrate digital payments in their business operations. This study aims to identify the influence of technological aspect (perceived benefits of implementing the digital payments), organizational aspect (length of business operations), and environmental aspect (the presence of competitors) on the MSME actors’ decisions to implement  the digital payments in Salatiga City using the Technological, Organizational, and Environmental (TOE) Theory. By employing the logit regression analysis, the results of this study demonstrate that the TOE theory does not completely apply to the MSME actors’ decision-making behavior of implementing the digital payments in Salatiga City. Further, this study highlights that only the perceived benefits of implementing the digital payments of the technological aspect which have a positive and significant influence on the MSME actors’ decisions to implement the digital payments IN Salatiga City. Meanwhile, the organizational aspect of technology infrastructure and length of business operations, and the environmental aspect of the presence of competitors have been confirmed to have no influence. The policy implications of these findings suggest the government as the stakeholders to adopt policies related to the issues in implementing the digital payments and the Bank Indonesia program towards a cashless society in 2025, and there is a need to increase digital literacy for the MSME actors in Salatiga City to remain competitive in this increasingly fast era of technology advancement.